Fetal effects of combined spinal‐epidural vs epidural labour analgesia: a prospective, randomised double‐blind study. (May 2014) - Patel, N. P.; El‐Wahab, N.; Fernando, R.; Wilson, S.; Robson, S. C.; Columb, M. O.; Lyons, G. R.
Summary We have compared fetal heart rate patterns, Apgar scores and umbilical cord gas values following initiation of labour analgesia using either combined spinal‐epidural or epidural. One hundred and fifteen healthy women requesting neuraxial analgesia in the first stage of labour were randomly assigned to receive either combined spinal‐epidural (n = 62) or epidural analgesia (n = 53). Fetal heart rate traces, recorded for 30 min before and 60 min after neuraxial block, were categorised as normal, suspicious or pathological according to national guidelines. Sixty‐one fetal heart rate tracings were analysed in the combined spinal‐epidural group and 52 in the epidural group. No significant differences were found in fetal heart rate patterns, Apgar scores or umbilical artery and vein acid‐base status between groups. However, in both combined spinal‐epidural and epidural groups, there was a significant increase in the incidence of abnormal fetal heart rate patterns following neuraxial analgesia (p < 0.0001); two before compared with eight after analgesia in the combined spinal‐epidural group and zero before compared with 11 after in the epidural group. These changes comprised increased decelerations (p = 0.0045) (combined spinal‐epidural group nine before and 14 after analgesia, epidural group four before and 16 after), increased late decelerations (p < 0.0001) (combined spinal‐epidural group zero before and seven after analgesia, epidural group zero before and eight after), and a reduction in acceleration rate (p = 0.034) (combined spinal‐epidural group mean (SD) 12.2 (6.7) h−1 before and 9.9 (6.1) h−1 after analgesia, epidural group 11.0 (7.3) h−1 before and 8.4 (5.9) h−1 after). These fetal heart rate changes did not affect neonatal outcome in this healthy population.